2012
DOI: 10.5535/arm.2012.36.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Findings of Acute Severe Lower Back Pain

Abstract: ObjectiveTo determine abnormal MRI findings in adults hospitalized with acute severe axial LBP.MethodSixty patients with back pain were divided into 3 groups consisting of 1) 23 adults with acute axial severe LBP who could not sit up or stand up for several days, but had not experienced previous back-related diseases or trauma (group A), 2) 19 adults who had been involved in a minor traffic accident, and had mild symptoms but not limited mobility (group B), and 3) 18 adults with LBP with radicular pain (group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…This amalgamation of dense protein structures allows the annulus to withstand the gravitational and mechanical forces translated through the vertebral bodies. Disruption of the posterior annulus may be seen on MRI imaging as a high intensity zone (HIZ) which may develop into a disc protrusion [ 51 , 52 ]. Furthermore, The HIZ has been shown to harbor increased levels of tumor necrosis factor alpha [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…This amalgamation of dense protein structures allows the annulus to withstand the gravitational and mechanical forces translated through the vertebral bodies. Disruption of the posterior annulus may be seen on MRI imaging as a high intensity zone (HIZ) which may develop into a disc protrusion [ 51 , 52 ]. Furthermore, The HIZ has been shown to harbor increased levels of tumor necrosis factor alpha [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that patients with HIZ had more disability improvement than those without HIZ after PDD. Kim et al [ 22 ] reported that the incidence of HIZ was significantly higher in patients with acute severe lower back pain than in patients in the control groups. Kang et al [ 23 ] also showed HIZ has meaning when it accompanies disc protrusion.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar IDD versus LBP in general population. Table 3 shows the studies to date that investigated the association between lumbar IDD and LBP in the general population 11,12,38,43,60,61) . A positive association between IDD and LBP has been observed in the general population by many research groups.…”
Section: Part II Correlation Between Lumbar Idd and Lbpmentioning
confidence: 99%
“…We reviewed clinical papers investigating the correlation between IDD and LBP, especially in non-athletes 11,12,38,43,60,61) . All of the papers showed the same result, a significant correlation between IDD and LBP; therefore, we believe these clinical papers have several common features.…”
Section: Clinical Researchmentioning
confidence: 99%
See 1 more Smart Citation